Exhumation of the Coastal Metamorphic Belt Above the Subduction‐to‐Transform Transition, in the Southeast Caribbean Plate Corner. Issue 8 (12th August 2021) - Arkle, Jeanette C.; Weber, John; Enkelmann, Eva; Owen, Lewis A.; Govers, Rob; Jess, Scott; Denison, Chris; O'Sullivan, Paul B.; Donelick, Raymond A.
Abstract: Plate corners that transition from subduction to transform motion can result in complex deformation. The southeastern corner of the Caribbean plate is a site where active westward subduction of the oceanic South American plate transitions to transform motion along continental South America. The Northern Range (Trinidad) and Paria (Venezuela) metamorphic mountains are located directly above this eastward propagating plate transition zone. We examined the exhumation history of the Northern Range and eastern Paria using apatite fission track (AFT) and apatite and zircon (U‐Th)/He (AHe and ZHe, respectively) thermochronology on 21 bedrock samples. These samples yield ages of ∼43–6 Ma (ZHe: aliquots), ∼20–4 Ma (AFT: pooled) and ∼5–2 Ma (AHe: aliquots). Along strike of the mountains, our new and published samples show a gradual eastward increase in age. Thermal modeling reveals two phases of rapid cooling and inferred exhumation that post‐dates oblique collision and that migrated from west to east. We record an ∼six‐fold increase in cooling and exhumation between ∼13–9 Ma in the Paria Peninsula and western Northern Range; a deceleration followed this rapid exhumation at ∼7 and 5 Ma. Synchronous with the deceleration in the west, exhumation of the eastern Northern Range increased ∼4 Ma. These post‐collisional changes in exhumation constrain the inversion to east‐side‐up tilting of the Northern Range to ∼4 Ma. We interpret the timing and pattern of exhumation since the mid‐Miocene to be consistent with the time‐transgressive processes produced by an eastward propagating lithospheric subduction‐transform edge propagator fault. Key Points: Thermal modeling reveals two phases of rapid cooling and inferred exhumation after oblique collision The inversion to east‐side‐up tilting of the Northern Range is constrained to ∼4 Ma Deformation and exhumation are consistent with the time‐transgressive processes produced by a propagating lithospheric subduction‐transform edge propagator fault